Anti‐Müllerian hormone concentration is associated with central adiposity and reproductive hormones in expectant fathers. (28th March 2022) - Hadlow, Narelle C.; Brown, Suzanne J.; Lim, Ee Mun; Prentice, David; Pettigrew, Simone; Cronin, Sophie L.; Prescott, Susan L.; Silva, Desiree; Yeap, Bu B.
Summary: Objective: The role of the anti‐Müllerian hormone (AMH) as an indicator of physical and reproductive health in men is unclear. We assessed the relationships between AMH and follicle‐stimulating hormone (FSH), luteinizing hormone (LH), testosterone, and metabolic parameters, in a cohort of expectant fathers. Design: ORIGINS Project prospective cohort study. Setting: Community‐dwelling men. Participants: Partners of pregnant women attending antenatal appointments. Main Outcome Measures: Serum AMH, FSH, LH, testosterone, and metabolic parameters. Results: In 485 expectant fathers, median age 33 years, median AMH was 40 pmol/L (quartiles 29, 56). AMH was inversely correlated with FSH, age, and body mass index (BMI) (correlation coefficients: −.32, −.24, and −.17 respectively). The age association was nonlinear, with peak AMH between 20 and 30 years, a decline thereafter, and somewhat steady levels after 45 years. The inverse association of AMH with FSH was log‐linear and independent of age and BMI ( β : −.07, SE: 0.01, p < .001). AMH was inversely correlated with waist circumference and directly associated with sex hormone‐binding globulin. Testosterone was moderately correlated with AMH (correlation coefficient: .09, β : .011, SE: 0.004, p = .014): this association was mediated by an inverse relationship with BMI (mediated proportion 0.49, p < .001). Conclusions: In reproductively active men, lower AMH is a biomarker for advancing age, and for poorer metabolic and reproductive health. The inverse association between AMH and FSH is independent of age and BMI, whereas the association of AMH and testosterone is mediated via BMI. The utility of AMH to predict reproductive and cardiometabolic outcomes in men warrants further investigation.